2020
DOI: 10.1063/5.0002537
|View full text |Cite
|
Sign up to set email alerts
|

Jumping droplets electronics cooling: Promise versus reality

Abstract: Electrifying both stationary and mobile systems requires ultra-compact, lightweight power electronics and electric machines. Increasing the volumetric and gravimetric density of these systems is constrained, however, by the capacity to remove heat from these assemblies. A promising method for extracting heat is jumping droplet condensation, which can address both spatially and temporally changing hotspots. Yet, disagreement exists in the literature about the maximum attainable heat flux for water-based, drople… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…When two or more droplets coalesce on a superhydrophobic surface, the merged droplet can jump spontaneously from the surface without requiring any external energy. , This phenomenon is defined as “coalescence-induced droplet jumping,” which has received significant attention owing to its potential in a variety of applications, including anti-icing, self-cleaning, condensation heat transfer, energy harvesting, , thermal diodes, electronics cooling, and atmospheric corrosion protection; , in these applications, a higher jumping velocity or height is always expected and favorable. When two droplets coalesce, the released excess surface energy is partly converted into kinetic energy, resulting in translational motion, but the energy conversion efficiency is inefficient. The jumping velocity V j for two equal size droplets coalesced on a flat superhydrophobic surface follows the capillary-inertial scaling, , V j ∼ u ic = , where u ic is the capillary-inertial velocity; γ, ρ, and r are the surface tension, density, and initial radius of the droplets, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…When two or more droplets coalesce on a superhydrophobic surface, the merged droplet can jump spontaneously from the surface without requiring any external energy. , This phenomenon is defined as “coalescence-induced droplet jumping,” which has received significant attention owing to its potential in a variety of applications, including anti-icing, self-cleaning, condensation heat transfer, energy harvesting, , thermal diodes, electronics cooling, and atmospheric corrosion protection; , in these applications, a higher jumping velocity or height is always expected and favorable. When two droplets coalesce, the released excess surface energy is partly converted into kinetic energy, resulting in translational motion, but the energy conversion efficiency is inefficient. The jumping velocity V j for two equal size droplets coalesced on a flat superhydrophobic surface follows the capillary-inertial scaling, , V j ∼ u ic = , where u ic is the capillary-inertial velocity; γ, ρ, and r are the surface tension, density, and initial radius of the droplets, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, nature-inspired functional surfaces, such as lotus leaves, cacti, and gecko skins, have facilitated an increased understanding of superhydrophobicity. Superhydrophobic surfaces show apparent advancing contact angles exceeding 150° with contact angle hysteresis below 10° . When two droplets coalesce on superhydrophobic surfaces, the released excess surface energy can be partly converted into kinetic energy, resulting in droplet jumping from the symmetry-breaking surface. Superhydrophobic surfaces having a range of structure length scales and surface chemistries have been widely used to improve anti-icing, self-cleaning, and condensation heat transfer performance. To gain a mechanistic understanding of droplet jumping, a plethora of studies have focused on the hydrodynamics of coalescence-induced droplet jumping, ,, droplet size effects, jumping velocity, , energy conversion efficiency, and jumping direction on superhydrophobic surfaces. These studies have conclusively shown that surface topography, wettability, droplet size, and liquid properties strongly affect coalescence hydrodynamics.…”
Section: Introductionmentioning
confidence: 99%
“…These results exhibit the clear and remarkable potential of integrating nanostructuring with the AM design process for the creation of codesigned and truly optimized devices for a plethora of energy applications such as heat pumps, [ 3 ] surface condensers [ 29 ] and electronics cooling systems. [ 30 ]…”
Section: Introductionmentioning
confidence: 99%